Slab corner effect on torsional behaviour of perimeter beams under missing column scenario - Pham, Anh Tuan (2019)
Perimeter beams in reinforced-concrete buildings are subjected to considerable torsion from slab negative bending moments. In the event of progressive collapse caused by column removals, torsion effects on such beams become critical, owing to redistribution of loads. The aim of this study is to explore the effects of slab corners on the torsional behaviour of perimeter beams in reinforced concrete beam–slab buildings, particularly in the case of column loss. A series of torsional tests on peripheral beams was conducted, comparing cases with and without slabs. Thereafter, physics-based numerical models were developed, based on the test results, to investigate the effect of varying the slab's parameters, such as thickness and reinforcement ratio, on torsional capacity. The models showed that the presence of reinforced concrete slabs could increase the torsional strength of perimeter beams by as much as 97%. The enhancement came first from the slab corner, which acted as a set of compressive struts. This effect increased with increasing slab thickness. It was also observed that the slab corners tend to shift torsional failure (which occurred at the twisted beam near the support) to about one beam depth away. The contribution of negative bending moment from slab reinforcement along the edges could also enhance overall structural capacity.